1998
DOI: 10.1007/s003830050258
|View full text |Cite
|
Sign up to set email alerts
|

Septic complications after splenectomy for sickle cell sequestration crisis

Abstract: Patients with sickle cell disease (SCD) are predisposed to infections. There is a paucity of recent information on the incidence of post-splenectomy infectious complications in these patients. The purpose of this study was to determine whether splenectomy increases infectious complications in SCD. Twenty-nine patients with SCD had splenectomy for sequestration crises at our hospital between 1988 and 1992; 16 of them received all of their follow-up care at our institution. These 16 charts were reviewed for infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
4
0
6
Order By: Relevance
“…A case series study of sickle-cell patients splenectomized from 1988 to 1992 showed no statistical difference in the incidence of sepsis before and after splenectomy, 16 a result similar to that observed by Kalpatthi et al., who performed a retrospective cohort study of 58 patients and also found no difference in the risk of invasive infections before and after surgery. 17 The risk of invasive infection, especially pneumococcal, in children with sickle-cell disease is the highest in the first 3 years of life and significantly decreases after the age of 5.…”
Section: Discussionsupporting
confidence: 83%
“…A case series study of sickle-cell patients splenectomized from 1988 to 1992 showed no statistical difference in the incidence of sepsis before and after splenectomy, 16 a result similar to that observed by Kalpatthi et al., who performed a retrospective cohort study of 58 patients and also found no difference in the risk of invasive infections before and after surgery. 17 The risk of invasive infection, especially pneumococcal, in children with sickle-cell disease is the highest in the first 3 years of life and significantly decreases after the age of 5.…”
Section: Discussionsupporting
confidence: 83%
“…However, only 16% of these children received immunization against H influenzae and pneumococcus, and none received the N meningitidis vaccine. Another study of 29 patients observed for 4 years demonstrated no significant difference in number of sepsis episodes per year before and after splenectomy performed around the second birthday [15]. This study used penicillin prophylaxis and preoperative Pneumovax vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…As a means to prevent future acute splenic sequestration crisis, elective splenectomy has been indicated in children older than 2 or 3 years of age after the first episode of the crisis. 10,11 Hypersplenism is defined as a clinical syndrome characterised by splenic enlargement, any combination of anaemia, leukopenia or thrombocytopenia, compensatory bone marrow hyperplasia and improvement after splenectomy. The patients become transfusion dependent to maintain haemoglobin level.…”
Section: Discussionmentioning
confidence: 99%